Non‐invasive telemonitoring improves outcomes in heart failure with reduced ejection fraction : a study in high‐risk patients - Nunes-Ferreira, Afonso (2020)
© 2020 The Authors. ESC Heart Failure published by John Wiley & Sons Ltd on behalf of the European Society of Cardiology. This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.